Prediction of Fiber Reinforced Concrete Strength Properties by Micromechanics Method - Shriganesh Shantikumar Kadam; V. V. Karjinni; C. S. Jarali (Salehan Institute of Higher Education, 2019)
High strength steel fiber reinforced concrete (HSSFRC) was prepared with the help of steel fiber. 0.5%, 1.0%, and 1.5% steel fiber by volume of concrete specimen was used in concrete for present investigation. Compressive strength test and flexural strength test were conducted on cubical and prismatic specimens respectively.The main objective of the research work is to validate the experimental out comes by a numerical technique such as micromechanics approach. A high strength steel fiber reinforced concrete whose compressive strength is greater than 60 N/mm2 was prepared and tested on concrete testing machine. Flexural strength test was conducted on universal testing machine to evaluate the bending properties of concrete. It was observed that with increase in the percentage of steel fiber volume the compressive strength and flexural strength also increases. However the workability of concrete declines and concrete is no longer in working condition. Micromechanics technique helps to predict the strength properties which save time required for casting and such technique was found to be beneficial.